ANALISIS PENURUNAN TARIF PAJAK PENGHASILAN BADAN TERHADAP KEEKONOMIAN KONTRAK BAGI HASIL GROSS SPLIT DAN MULTIPLIER EFFECT BAGI PEREKONOMIAN PADA KEGIATAN HULU MINYAK BUMI DI INDONESIA - Gregorius Bela Prasetya (Scientax, 2021)
Analysis of declining income tax rate of economics on production sharing contract gross split and multiplier effect for the economy in upstream activity in Indonesia describes about Indonesia’s Government announces regulation of production sharing contract gross split in upstream activity for contractor to invest in oil and gas in Indonesia. Due to the pandemic of COVID-19, the Government of Indonesia announced another regulation in regard to income tax rate reduction. This has positively affected the economics on NPV and IRR of contractor and has triggered multiplier effects for the economy in general. Sensitivity analysis is used to calculate the effect of income tax rate reduction for the economics in gross split and multiplier effect. This research has shown that 1% of declining income tax rate affects US$29,333,000 of NPV, 0.3% of IRR, US$20,533,000 Gross Domestic Product and 2,933 jobs in pessimistic scenario; US$61,107,000 of NPV, 0.5% of IRR, US$42,775,000 Gross Domestic Product and 6,111 jobs in moderate scenario; and US$92,881,000 of NPV, 0.6% of IRR, US$65,016,000 Gross Domestic Product and 9,288 jobs in optimistic scenario.